Gestión de calidad en la atención de pacientes con pie diabético en el Hospital General Machala. - Tivillin Chávez, Ana Karina (My University, 2025)
Quality Management (QM) is effective across the entire healthcare facility when it is evaluated frequently. In this regard, one approach to assessing QM in healthcare is the use of quality indicators, proposed by the Avedis Donabedian Model (ADM), which are classified into three elements: Structure, Process, and Outcomes. Objective: To evaluate QM in the care processes for patients with Diabetic Foot (DF) at Machala General Hospital. Methodology: This study featured a descriptive, cross-sectional design with a quantitative approach. The population consisted of 120 nursing professionals working at the IESS General Hospital and 60 patients diagnosed with DF. A Google Form was used to survey staff, and the PSQ questionnaire was used for patient surveys. Results: The most widely represented unit was Clinical Hospitalization 1 (24.17%), while the DF area (2.50%) showed a low staffing level. The largest proportion of staff (45.83%) has between 6 and 10 years of experience. Regarding the Structure dimension assessed under the MAD, the most representative category was "Good" (32.50%). Regarding the Process dimension, 66.66% perceived the quality of care as positive (good or excellent). In the Results dimension, 21.67% rated care as fair and 5.83% as poor. Regarding the perception of care and administrative barriers in the management of patients with PD complications, overall satisfaction reported a mean of 7.13 (SD = 0.982). All Spearman correlations (CG, Process, and Results) were statistically significant. Conclusions: The findings demonstrated that, in order to propose strategies aimed at improving care, it is important to focus efforts on the identified areas of opportunity, especially communication and financial aspects
La Gestión de Calidad (GC) es eficaz a nivel de todo el establecimiento de la salud cuando la misma se evalúa con frecuencia. En ese sentido, un enfoque para evaluar la GC en la atención en salud es el uso de indicadores de calidad, propuesto por el Modelo de Avedis Donabedian (MAD), los cuales se clasifican en tres elementos: Estructura, Proceso y Resultados. Objetivo: Evaluar la GC en los procesos de atención a los pacientes con Pie Diabético (PD) del Hospital General Machala. Metodología: Estudio con diseño descriptivo de corte transversal, con un enfoque cuantitativo. La población estuvo conformada por 120 profesionales de enfermería que laboran en el Hospital General IESS y 60 pacientes con diagnóstico de PD. Se utilizó el Formulario de Google para encuestar al personal y el Cuestionario PSQ para los pacientes. Resultados: Las unidades con mayor representación fue Hospitalización Clínica 1 (24,17%), mientras que el área de PD (2,50%) evidenció una escasa asignación de personal. La mayor proporción del personal (45,83%) cuenta con una experiencia intermedia entre 6 y 10 años. Sobre la dimensión Estructura evaluada bajo el MAD, la categoría más representativa fue “Buena” (32,50%). Acerca de la dimensión Proceso, el 66,66% percibió como positiva (buena o excelente) la calidad de atención. En la dimensión Resultados, el 21,67% calificó la atención como regular y un 5,83% como deficiente. Respecto a la percepción de barreras asistenciales y administrativas en el manejo de pacientes con complicaciones de PD, la satisfacción general reportó una media de 7,13 (DE = 0,982). Todas las correlaciones de Spearman (GC, Proceso y Resultados) fueron estadísticamente significativas. Conclusiones: Los hallazgos demostraron que, para proponer estrategias orientadas a mejorar la atención, es importante focalizar los esfuerzos en las áreas de oportunidad identificadas, especialmente en la comunicación y los aspectos financieros.
Keywords: CALIDAD DE LA ATENCIÓN DE SALUD; PIE DIABÉTICO; MODELO DE DONABEDIAN